Extracellular vesicles from thyroid cancer harbor a functional machinery involved in extracellular matrix remodeling - Bravo Miana, Rocío del Carmen (2022)
Extracellular vesicles (EVs) participate in cell-stroma crosstalk within the tumor microenvironment and fibroblasts (Fb) contribute to tumor promotion in thyroid cancer. However, the role of tumor-stroma derived EVs still needs to be deciphered. We hypothesized that the interaction of thyroid tumor cells with Fb would liberate EVs with a specific proteomic profile, which would have an impact on EV-functionality in thyroid tumor progression-related events. Tumor (TPC-1, 8505c) and non-tumor (NThyOri) thyroid cells were co-cultured with human Fb. EVs, obtained by ultracentrifugation of conditioned media, were characterized by nanoparticle tracking analysis and western blotting. EV-proteomic analysis was performed by mass-spectrometry, and metalloproteinases (MMPs) were studied by zymography. EV-exchange was evaluated using immunofluorescence, confocal microscopy and FACS. EVs expressed classical exosome markers, with EVs from thyroid tumor cell-Fb co-cultures showing a proteomic profile related to extracellular matrix (ECM) remodeling. Bidirectional crosstalk between Fb and TPC-1 cells produced significantly more EVs than their isolated cells, and potentiated EV-functionality. In line with this, Fb-TPC-1 derived EVs induced MMP2 activation in NThyOri supernatants, and MMP2 activity could be evidenced in Fb and TPC-1 contact-independent co-cultures. Besides, MMP2 interactors allowed us to discriminate between EVs from thyroid tumoral and non-tumoral milieus. Interestingly, Fb internalized more EVs from TPC-1 than from NThyOri producing cells. Fb and thyroid tumor cell crosstalk produces specialized EVs with an ECM remodeling proteomic profile, enabling activation of MMP2 and possibly facilitating ECM-degradation, which is potentially linked with thyroid tumor progression.